Registration of Mortgage Rights that Exceed the Time Limit at the Agrarian and Spatial Planning Office/National Land Agency Based on Law Number 4 of 1996 in Tasikmalaya City - Noor, Aslan; Anita, Dewi; Wijaya, Anandya Tasya; Adiwijaya, Ratna Sari Putri (Journal of Law, Politic and Humanities, 2024)
Mortgage is defined as a security right imposed on land rights. On 19 April 1996, Law Number 4 of 1996 on Mortgage Rights over land and objects related to land (UUHT) was enacted. This system is regulated in PMATR/KBPN Number 5 of 2020 concerning electronically integrated Mortgage Rights Services, which aims to provide certainty and legal protection in utilising land as an object of Mortgage Rights. This research examines how the registration of Mortgage Rights that exceeds the time limit at the ATR / BPN Office based on UUHT Number 4 of 1996 in Tasikmalaya City and what are the legal consequences if the registration of the Deed of Granting Mortgage (APHT) exceeds the time limit at the Agrarian and Spatial Planning Office / National Land Agency.The research method used is Empirical Juridical, with data sources from the ATR / BPN Office of Tasikmalaya City, PPAT, and Mortgage Rights Applicants in Tasikmalaya City. The data collection technique uses primary and secondary data. The results show that the process of encumbering Mortgage Rights in Tasikmalaya City often exceeds the time limit of 7 working days stipulated by UUHT article 13 paragraph (2), with an average delay of 0.28% during January to July 2024. The legal consequences are administrative sanctions in the form of verbal warnings. This delay does not cause the cancellation of Mortgage Rights, but the law cannot provide optimal protection to creditors according to the purpose of the certificate of mortgage rights.